Elite swimmers and the D allele of the ACE I/D polymorphism - Woods, D.; Hickman, M.; Jamshidi, Y.; Brull, D.; Vassiliou, V.; Jones, A.; Humphries, S.; Montgomery, H. (Human Genetics, 2001)
A polymorphism of the human angiotensin-1-converting enzyme (ACE) gene has been identified in which the presence (insertion, I allele) of a 287-bp fragment rather than the absence (deletion, D allele) is associated with lower ACE activity. Several recent studies have shown an association of the I allele with endurance performance, it being found with excess frequency in elite distance runners, rowers and mountaineers. Other workers using heterogeneous cohorts of athletes from mixed sporting disciplines have found no such association. An increasing linear trend of I allele frequency with the distance run amongst Olympic runners and an excess of the D allele amongst sprinters led us to examine whether the ratio of I and D alleles in swimmers competing over different distances would also vary. Swimmers (n=120) from the European and Commonwealth championships and an American college team had their ACE genotype determined and their gene and allele frequencies compared with several control groups, the most closely age-matched of which were 1248 military recruits. Of the 103 Caucasians, there was a significant excess of the D allele compared with this control group only in the truly elite swimmers of the European and Commonwealth championships (P=0.004). This association remained in those competing over shorter distances (P=0.005 for 400 m and below) but not in the longer events. These findings were confirmed in three further large control groups. A population association study testing whether a genetic marker (the ACE I/D polymorphism) occurs more frequently in cases (elite athletes) than in controls therefore requires a homogeneous cohort of subjects from the same sporting discipline.